Decreasing Patient Radiation Exposure from Computed Tomography for Hip Preservation Surgery - Marland, Jennifer D.; Smythe, Jason; Barlow, Daniel; Whiting, Daniel; Payne, Brayden; West, Hugh S.; Wylie, James D. (The Journal of Hip Surgery, 2023)
This article describes how we were able to decrease patient radiation exposure from hip computed tomography (CT) for hip preservation evaluation without a degradation of image quality. This is a retrospective review of a quality improvement project. The study included patients who underwent hip CT at a single center as part of a clinical evaluation for young adult hip pain. Four distinct protocols were used during the study period. All protocols included at CT scan of the hip with slices through the distal femur to evaluate femoral version. Patient variables collected included age, gender, and body mass index (BMI). The dose–length product was collected and the effective dose in millisieverts (mSv) was calculated. Differences in dose between protocols were compared using analysis of variance with appropriate post hoc tests and multivariate general linear regression. A total of 613 patients underwent hip CT during the study period with 304 patients in protocol 1, 83 in protocol 2, 136 in protocol 3, and 91 in protocol 4. When controlling for age, gender, and BMI there was a significant decrease in effective dose of radiation from protocol 1 (3.63 mSv) to protocol 2 (3.06 mSv) (p = 0.002) and protocol 2 (3.06 mSv) to protocol 3 (2.16 mSv) (p < 0.001). There was no difference between protocol 3 (2.16 mSv) and protocol 4 (2.10 mSv) (p = 0.269) but protocol 4 was easier to administer. In regression modeling, BMI (p < 0.001) and protocol used (p < 0.001) were independent predictors of effective radiation dose (model R2 = 0.585). Through a longitudinal clinical quality improvement project, we were able to decrease the effective radiation exposure to patients undergoing hip CT for hip preservation evaluation by close to 50%. Only CT protocol used and patient's BMI were predictors of ionizing radiation exposure.Level of Evidence Level 3, retrospective comparative study.
Keywords: hip preservation; computed tomography; radiation; hip arthroscopy